Chapter The Luwian Goddess Darawa - Hutter, Manfred (Studia Asiana, 2023)
The PN Kammalia-Tarawa in an Old Assyrian tablet seems to be the earliest reference of the deity Darawa. The Luwian background this deity is also apparent, e.g., from the plural form DDa-ra-ú-wa-an-zi or from those texts mentioned in CTH 457 and the etymological interpretation of the divine name to the Luwian verb tarāwi(ya)-. Since the early Middle Hittite period Darawa also found her way into the Hattian milieu and as a goddess connected with the family life, she is mentioned several times in festivals for a queen (CTH 646), but also in the Hittite Prayer to the Sun-goddess of the Netherworld (CTH 371) which is - in my opinion - the only Hittite texts mentioning Darawa within the "pantheon of the state". Texts from the Hurrian and Kizzuwatnaean milieu (e.g., CTH 351) also refer several times to Darawa, but this is clearly the result of a secondary and marginal dissemination of the goddess. In conclusion one might say that Darawa from her Luwian background also came into contact with various milieus of the "Hittite pantheon", functioning as a goddess providing good (and evil) to humans in everyday life.